2015
DOI: 10.1589/jpts.27.3883
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between energy cost and the center of gravity trajectory during sit-to-stand motion

Abstract: [Purpose] The purpose of this study was to examine the relationship between jerk cost and the formation of the center of gravity trajectory during sit-to-stand motion with asymmetrical foot placement. [Subjects] Nineteen male volunteers were included (age: 21 ± 1 years). [Methods] The subjects moved from a sitting position to a standing position under two different foot placement conditions: (1) 0 degrees of dorsiflexion on the non-dominant side and 20 degrees of dorsiflexion on the dominant side (P1) and (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, Fukuda et al also reported that the relationships between motor coordination and the craniocervical and thoracolumbar joints and the thoracolumbar and pelvic joints were non-linear. Consistent with the report by Fukuda et al 13 ) , we also believe that the craniocervical joint underwent the largest angular changes while in the standing position, possibly as a motor strategy selected for minimizing energy costs 1 ) . That is, tensile force generated by muscle moment is necessary for the initial body rotation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Fukuda et al also reported that the relationships between motor coordination and the craniocervical and thoracolumbar joints and the thoracolumbar and pelvic joints were non-linear. Consistent with the report by Fukuda et al 13 ) , we also believe that the craniocervical joint underwent the largest angular changes while in the standing position, possibly as a motor strategy selected for minimizing energy costs 1 ) . That is, tensile force generated by muscle moment is necessary for the initial body rotation.…”
Section: Discussionsupporting
confidence: 91%
“…Movements requiring multi-joint motor coordination, such as walking, standing, and turning, occur frequently in daily life. Efficient locomotion patterns are realized as a result of multi-joint motor coordination guided by the principle of conservation of energy cost 1 ) in the execution of specific tasks, such as the forward reach 2 ) , squat 3 , 4 , 5 ) , and maintenance of a tandem stance 6 , 7 ) . In the field of physical therapy, deviations from a normal manner established for each type of movement due to disease are used to estimate the degree of dysfunction; therefore, understanding motor coordination between adjacent joints is essential for clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…Forward tilt pattern was selected by all participants at AP-N and MP-N (Table 1). Previous research revealed motor pattern of activity of daily living (ADL) is taken motor pattern to minimize the energy cost7,8,9 ) . Thus, the forward tilt pattern was used the most frequently at N to minimize the energy cost by the generation of the COG-COP moments arm.…”
Section: Discussionmentioning
confidence: 99%